Caribbean Jewish Crossings : Literary History and Creative Practice - Kaufman, Heidi, 1969-; Casteel, Sarah Phillips, 1974- (Book collections on Project MUSE., 2019)
"This books highlights the historical convergence of African and Jewish immigrants to the Caribbean Islands by comparing their literatures of oppression, migration, and survival"--